2018
DOI: 10.1590/1984-0462/;2018;36;4;00010
|View full text |Cite
|
Sign up to set email alerts
|

Características Socioeconômicas E Nutricionais De Crianças E Adolescentes Com Anemia Falciforme: Uma Revisão Sistemática

Abstract: Objective: To describe the socioeconomic and nutritional characteristics of children and adolescents with sickle cell anemia.Data sources: The present study is a systematic literature review based on published scientific articles. The searches were carried out using the electronic database of the National Library of Medicine, National Institutes of Health- PubMed. Two searches of articles published in the last 20years and without limitation of language were carried out. Thefirst one started from the Medical Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
1
21
1
8
Order By: Relevance
“…SCD patients have delayed physical as well as sexual development 4. These are consequences of various factors like poor nutrition, repetitive infections, blood transfusions, painful crisis, and frequent hospital admissions 5. The onset of menarche is delayed in women with SCD4,6 and is strongly associated with the HbSS phenotype compared to the HbSC phenotype 7.…”
Section: Methodsmentioning
confidence: 99%
“…SCD patients have delayed physical as well as sexual development 4. These are consequences of various factors like poor nutrition, repetitive infections, blood transfusions, painful crisis, and frequent hospital admissions 5. The onset of menarche is delayed in women with SCD4,6 and is strongly associated with the HbSS phenotype compared to the HbSC phenotype 7.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, both the child and the adolescent affected by the disease, as well as their family caregivers, are faced with a situation marked by a chronic stress linked to the disease, which extends throughout the treatment and permeates their daily lives (Figueiró & Ribeiro, 2017;Gomes et al, 2019;Jesus, Konstantyner, Lobo, & Braga, 2018;Rodrigues, Araújo, & Melo, 2010;Santos, Damião, Fonseca, Rodrigues, & Aguiar, 2019); being indicated that intervention proposals are directed both to the child (Campelo et al, 2018;Oliveira, Enumo, & Paula, 2017) and to the family (Caprini, 2019;Figueiredo, Moreira, Mota, Oliveira, & Gomes, 2019).…”
mentioning
confidence: 99%
“…However, these data should be interpreted with caution because, in our study, the question was asked of the children at time T, and the data were not available at the end of schooling, so we could not calculate the actual delay rate. A study has shown that, in some countries, SCD children and adolescents had a lower level of education than the national average, particularly due to the social difficulties faced by the black ethnic groups to which these patients belong [ 28 ]. However, the study data did not include European patients.…”
Section: Discussionmentioning
confidence: 99%